Artificial Intelligence in Cybersecurity Threat Detection - Wang, Zehan (International Journal of Computer Science and Information Technology, 2024)
With the increasing frequency and complexity of cyberattacks, traditional cybersecurity threat detection methods have been difficult to cope with new types of threats. Artificial Intelligence (AI) technology, with its powerful data processing and pattern recognition capabilities, has gradually become an important tool for enhancing cyber security. This paper aims to explore the application of AI in cybersecurity threat detection, firstly outlining the current status of the development of AI technology in cybersecurity, and then focusing on analyzing the application of core methods such as machine learning and deep learning in threat detection, and discussing the advantages of integrated learning and multimodal methods. Finally, this paper summarizes the current challenges faced by AI technology in the field of cyber security and looks forward to the future development direction. Through the research in this paper, it is expected to provide reference for improving the accuracy and efficiency of cybersecurity threat detection.